(untitled) (diségno, 2023)
The continuous changes in the city imply a necessary rethinking of the tools –in the field of drawing and representation– to read, interpret and describe urban changes and contingent conditions in order to imagine possible futures. The drawing of projective geometry, as well as the hyper-realist tendency of representation, do not turn out to be suitable to return the ‘materials’ of the complex urban assemblage. Therefore, the present contribution aims to investigate the potential of two precise tools, the diagram and the collage. They are well established tools in the disciplinary sphere because they are elastic devices of knowledge and imagination. A theoretical-practical exploration is proposed that traces the origins, evolutions and drifts to contemporary experiments that, while fixing a precise image, refer to forms of imagination, demonstrating the different potentials of these tools. The diagram reducing and the collage assembling, have been protagonists of radical imaginaries and investigations of reality; it is no coincidence that the members of Team X, as well as the Radicals have used both tools producing a legacy of thought picked up by the architect of complexity, Koolhaas (and the generation of his students). A matrix that breaks into the age of figurative realism today and that, with digital tools, opens up a possible new phase of thinking to build complex maps and eclectic looks.